Meningkatkan Prestasi Belajar di Perguruan Tinggi dengan Mengembangkan Kecerdasan Emosional - Nikodemus Thomas Martoredjo (Bina Nusantara University, 2013)
To be successful in a particular field, someone does not only rely on academic ability or technical skills. There is another ability that has big contribution to determine the success, which is the ability to manage emotions well or emotional intelligence. It was found many cases which people have failed not because they lack of the potential for mastery of academic or technical skills but they lack of the skills to manage their emotions. Speaking about emotional intelligence, there are five things to consider: self-awareness, self control, motivation, empathy, and social skills. These five things work together in developing emotional intelligence. If emotional intelligence can be realized and well developed, it can be a benefit for students who are studying in universities. The hope is the systematic development of emotional intelligence will best promote student achievement in learning.